THE RELATIONSHIP BETWEEN MOTHERS’ KNOWLEDGE AND ATTITUDES TOWARD THE INTEREST IN USING IUD CONTRACEPTION AT WANAYASA PUBLIC HEALTH CENTER - Erlangga Zulfi Jihad Setyagama; Priyatin Sulistyowati; Dwi Astuti (PT. Jurnal Center Indonesia Publisher, 2025)
Background: The Family Planning Program (KB) is a government effort to control population growth in Indonesia. One of the contraceptive methods that is highly recommended in the KB program is the intra uterine device (IUD) or often called a spiral. IUD is a contraceptive that can be used in the long term with high effectiveness in preventing pregnancy, while having minimal risk of side effects if used correctly, but the number of IUD usage in Indonesia is still relatively low compared to other contraceptive methods. Research Objective: To determine the effect of knowledge and attitude on the interest of mothers in using IUD KB at the Wanayasa Health Center. Method: This study used a quantitative method with a sample of 66 respondents. Data analysis was carried out using bivariate and univariate, significance was determined if (p value <0.05). data processing was carried out using SPSS. Result: The results of the study showed that in the knowledge variable there were 37 respondents with good knowledge, 23 respondents with sufficient knowledge and 6 respondents with less knowledge. As for the attitude variable, there were 52 respondents with positive attitudes and 14 respondents with negative attitudes. The results of this study also show that there is an influence between knowledge and interest in mothers using IUD with P-Value = 0.003, while the attitude variable also shows that there is an influence between attitude and interest in mothers using IUD with P-Value = 0.010. Conclusion: there is a significant influence between knowledge on interest in mothers using IUD and attitude on interest in mothers using IUD